2018
DOI: 10.1007/s40333-018-0101-3
|View full text |Cite
|
Sign up to set email alerts
|

CO2, CH4 and N2O flux changes in degraded grassland soil of Inner Mongolia, China

Abstract: The main purpose of this study was to explore the dynamic changes of greenhouse gas (GHG) from grasslands under different degradation levels during the growing seasons of Inner Mongolia, China. Grassland degradation is associated with the dynamics of GHG fluxes, e.g., CO 2 , CH 4 and N 2 O fluxes. As one of the global ecological environmental problems, grassland degradation has changed the vegetation productivity as well as the accumulation and decomposition rates of soil organic matter and thus will influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 70 publications
0
2
1
Order By: Relevance
“…Although soil moisture is commonly considered a critical factor controlling methane production and oxidation, we found no correlation between soil moisture and the seasonal CH 4 uptake in this study. Our result differed from some other studies in grassland ecosystems (Bai et al, 2018;Dijkstra et al, 2013;Zhao et al, 2017), mainly due to that soil 10.1029/2019JG005011 Journal of Geophysical Research: Biogeosciences moisture is not the most important limiting factor in alpine meadow as that in the temperate semiarid steppe.…”
Section: Seasonal Dynamic and Its Controlscontrasting
confidence: 99%
“…Although soil moisture is commonly considered a critical factor controlling methane production and oxidation, we found no correlation between soil moisture and the seasonal CH 4 uptake in this study. Our result differed from some other studies in grassland ecosystems (Bai et al, 2018;Dijkstra et al, 2013;Zhao et al, 2017), mainly due to that soil 10.1029/2019JG005011 Journal of Geophysical Research: Biogeosciences moisture is not the most important limiting factor in alpine meadow as that in the temperate semiarid steppe.…”
Section: Seasonal Dynamic and Its Controlscontrasting
confidence: 99%
“…Other studies also found that soil temperature and soil moisture played the major role in driving the temporal CO 2 emission variation [35,36]. For example, Bai et al think that soil moisture and temperature were positively correlated with CO 2 emissions [35]. Sun et al obtained similar the same results of Bai et al, they pointed out that temporal variations of CO 2 emission were strongly correlated with air and sediment temperatures [36].These results suggest that higher soil temperatures affect the root systems, enhancing root respiration and microbiological activity along with soil organic matter mineralization [37].…”
Section: Ecosystem Respiration (Re)mentioning
confidence: 91%
“…Using a stepwise multiple regression analysis, the authors found that soil volumetric water content, soil temperature and aboveground green biomass were the three main factors that affect ecosystem respiration, and that aboveground green biomass was the primary factor related to ecosystem respiration [16]. Other studies also found that soil temperature and soil moisture played the major role in driving the temporal CO 2 emission variation [35,36]. For example, Bai et al think that soil moisture and temperature were positively correlated with CO 2 emissions [35].…”
Section: Ecosystem Respiration (Re)mentioning
confidence: 99%